2021
DOI: 10.1093/cdn/nzab013
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Microbiota in an Indigenous Population Is Associated with Maternal Factors, Stage of Lactation, and Breastfeeding Practices

Abstract: Background Human milk contains a diverse community of bacteria that are modified by maternal factors, but whether these or other factors are similar in developing countries has not been explored. Our objective was to determine whether milk microbiota was modified by maternal age, body mass index (BMI), parity, lactation stage, subclinical mastitis (SCM), and breastfeeding practices in the first six months of lactation in an indigenous population from Guatemala. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 108 publications
1
5
0
Order By: Relevance
“…At the genera level, we observed a shift from Corynebacterium, Staphylococcus, and Streptococcus in early lactation to Novosphingobium, Pseudomonas, Sphingobium, and Stenotrophomonas in late lactation. These findings align with previous results that analyzed the impact of the stage of lactation and confirmed a shift from early to late stage (Gueimonde et al, 2007;Collado et al, 2008;Cabrera-Rubio et al, 2012;Khodayar-Pardo et al, 2014;Latuga et al, 2014;Chen et al, 2018;Gonzalez et al, 2021;Lopez Leyva et al, 2021b). In a study at the species level (Gonzalez et al, 2021), we also observed a shift from Corynebacterium jeikeium, Lactobacillus gasseri, Staphylococcus hominis, Staphylococcus epidermidis, Streptococcus mitis, and Streptococcus parasanguinis species in early lactation to Sphingobium yanoikuyae, Pseudomonas putida, and Stenotrophomonas maltophilia species in late lactation, but this previous study only analyzed the stage of lactation and did not consider the type of breastfeeding practice (Gonzalez et al, 2021).…”
Section: Dominant Bacteriasupporting
confidence: 92%
See 1 more Smart Citation
“…At the genera level, we observed a shift from Corynebacterium, Staphylococcus, and Streptococcus in early lactation to Novosphingobium, Pseudomonas, Sphingobium, and Stenotrophomonas in late lactation. These findings align with previous results that analyzed the impact of the stage of lactation and confirmed a shift from early to late stage (Gueimonde et al, 2007;Collado et al, 2008;Cabrera-Rubio et al, 2012;Khodayar-Pardo et al, 2014;Latuga et al, 2014;Chen et al, 2018;Gonzalez et al, 2021;Lopez Leyva et al, 2021b). In a study at the species level (Gonzalez et al, 2021), we also observed a shift from Corynebacterium jeikeium, Lactobacillus gasseri, Staphylococcus hominis, Staphylococcus epidermidis, Streptococcus mitis, and Streptococcus parasanguinis species in early lactation to Sphingobium yanoikuyae, Pseudomonas putida, and Stenotrophomonas maltophilia species in late lactation, but this previous study only analyzed the stage of lactation and did not consider the type of breastfeeding practice (Gonzalez et al, 2021).…”
Section: Dominant Bacteriasupporting
confidence: 92%
“…Recently, we conducted a study in the Mam -Mayan indigenous community in Guatemala to identify maternal factors involved in modifying the human milk microbiome at both the genera ( Lopez Leyva et al, 2021b ) and species levels ( Gonzalez et al, 2021 ) and identified distinct clustering of microbial communities associated with both stages of lactation and breastfeeding practices. The study conducted at the species level reported a shift from Staphylococcus and Streptococcus species in early lactation to Sphingobium and Pseudomonas species in late lactation ( Gonzalez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, the maternal environment may program the infant gut microbiota for enhanced milk utilization via vertical microbial transmission. Thus far, parity effects on maternal microbiota have been demonstrated in agricultural species ( Berry et al., 2021 ; Bogado Pascottini et al., 2021 ), and more recently in humans ( Kervinen et al., 2021 ; Lopez Leyva et al., 2021 ). However, in pigs, parity effects extend to the infant gut microbiota, suggesting that such effects may be vertically transmitted from maternal reservoirs ( Berry et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ralstonia has also been demonstrated to reduce glucose tolerance in mice [61] , reduce renal function in patients with ulcerative colitis [29] , and linked to nosocomial infections in immunocompromised individuals [14] . Ironically, the enriched genus Leucobacter found in our control group was found to be among the most abundant genera in women's breast milk with a healthy body mass index, without subclinical mastitis, and with a more diverse microbiota, in contrast to their counterparts [38] .…”
Section: Discussionmentioning
confidence: 66%